Mismatch in Preferences for Working from Home – Evidence from Discrete Choice Experiments with Workers and Employers - Piotr Lewandowski; Katarzyna Lipowska; Mateusz Smoter (Institute of Labor Economics (IZA), 2023)
We study workers' and employers' preferences for remote work, estimating the willingness to pay for working from home (WFH) using discrete choice experiments with more than 10,000 workers and more than 1,500 employers in Poland. We selected occupations that can be done remotely and randomised wage differences between otherwise identical home- and office-based jobs, and between otherwise identical job candidates, respectively. We find that demand for remote work was substantially higher among workers than among employers. On average, workers would sacrifice 2.9% of their earnings for the option of remote work, especially hybrid WFH for 2-3 days a week (5.1%) rather than five days a week (0.6%). However, employers, on average, expect a wage cut of 21.0% from candidates who want to work remotely. This 18 pp gap in the valuations of WFH reflects employers' assessments of productivity loss associated with WFH (14 pp), and the additional effort required to manage remote workers (4 pp). Employers' and workers' valuations of WFH align only in 25-36% of firms with managers who think that WFH is as productive as on-site work.
Keywords: J21; J31; J81; 330; working from home; remote work; discrete choice experiment; willingness to pay